2021
DOI: 10.3390/nu14010199
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 2’-Fucosyllactose and Bifidobacterium longum Subspecies infantis on Growth, Organ Weights, and Intestinal Development of Piglets

Abstract: Human milk is rich in oligosaccharides that influence intestinal development and serve as prebiotics for the infant gut microbiota. Probiotics and 2’-fucosyllactose (2’-FL) added individually to infant formula have been shown to influence infant development, but less is known about the effects of their synbiotic administration. Herein, the impact of formula supplementation with 2’-fucosyllactose (2’-FL) and Bifidobacterium longum subsp. infantis Bi-26 (Bi-26), or 2’-FL + Bi-26 on weight gain, organ weights, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 59 publications
3
9
0
Order By: Relevance
“…Lastly, the disappearance of the effect of Bi-26 in the latency measure in the FLBI group suggests that the potential anxiolytic effect of Bi-26 may not translate to the synergistic effects of 2′-FL and Bi-26. This is consistent with the effect of 2′-FL on the presence of B. infantis in the ascending colon or rectum not translating to a synbiotic effect when co-administered with Bi-26 ( Daniels et al, 2022 ). Overall, further research is warranted to study potential anxiolytic effects of probiotics, especially B. infantis , and synbiotics with a properly validated behavioral model for anxiety in pigs.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Lastly, the disappearance of the effect of Bi-26 in the latency measure in the FLBI group suggests that the potential anxiolytic effect of Bi-26 may not translate to the synergistic effects of 2′-FL and Bi-26. This is consistent with the effect of 2′-FL on the presence of B. infantis in the ascending colon or rectum not translating to a synbiotic effect when co-administered with Bi-26 ( Daniels et al, 2022 ). Overall, further research is warranted to study potential anxiolytic effects of probiotics, especially B. infantis , and synbiotics with a properly validated behavioral model for anxiety in pigs.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, the effects of 2′-FL and B-26 individually and together on brain structural and behavioral development were assessed in young pigs. Results on growth performance and intestinal health outcomes of this study were previously reported ( Daniels et al, 2022 ).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations